Analysis of the Impact of Patriarchal Culture in Family Dynamics on Child Parenting and Emotional Development - Elizabeth Dewi Novianti; Anisatus Zahra Fitriani (Penerbit Jurnal Indonesia, 2026)
Patriarchal culture remains a part of Indonesia’s social structure that shapes society’s views on the roles of men and women. Within the family, patriarchal values play a major role in forming parenting patterns that affect children’s emotional and social development. This study aims to analyze the influence of patriarchal culture on family dynamics and its impact on children’s emotional balance. The research employed a qualitative method with a descriptive literature study approach by reviewing national journals published between 2020 and 2025. The findings indicate that patriarchy causes gender role inequality and differing parenting patterns between boys and girls, which can hinder their social and emotional development. However, modern families are beginning to show a shift toward egalitarian parenting patterns that emphasize gender equality and the emotional well-being of children.